Effect of Early Use of Botulinum Toxin A on Goal Attainment in Post-Stroke Spasticity - Atul Patel; Jinming Zhang; Simon Page; Sarah Harding; Mathieu Beneteau; Alberto Esquenazi (Toxicon, 2026)

Factors influencing species reintroduction success - Gemma Harding; Richard A. Griffiths; Simon A. Black (Biodiversity and Conservation, 2025)
Conservation reintroductions are widespread in species conservation but evaluation of their success, and particularly the reporting of failures is lacking. Here we evaluate aspects of species reintroduction that influence success and how conservation practitioners measure success. We analysed trends and reasons for perceived failure and success across 341 documented reintroduction case studies from across the globe. Reintroductions in Africa had lower scores for success compared to East Europe, North & Central Asia; fish had higher scores than invertebrates; and government and non-government organisations scored projects as more successful than did zoos or aquaria. Goals and Indicators do not appear to influence the success score, although too many goals may have a negative influence on success. Qualitative analysis of the reasons for failure and success showed that activities linked to Partnerships & Support (e.g. community support, government partnerships) were the most regularly cited reason for success, and Habitat & Release site (e.g. poor habitat connectivity, lack of suitable release sites) were the most frequently cited reason linked to failure, or failed elements. Current conservation efforts continue to comprise a disproportionately high number of reintroductions for mammals and birds compared to other taxa, and the number of reintroductions in developed countries outweigh those of developing countries.

The Fourth Global Coral Bleaching Event: Where do we go from here? - James Davis Reimer; Raquel S. Peixoto; Sarah W. Davies; Nikki Traylor-Knowles; Morgan L. Short; Rafael A. Cabral-Tena; John A. Burt; Igor Pessoa; Anastazia T. Banaszak; R. Scott Winters; Tom Moore; Verena Schoepf; et al. (Coral Reefs, 2024)

Marine resources and their value in Kadavu, Fiji - Simon Harding; Kalisiana Marama; Annette Breckwoldt; Ulamila Matairakula; Elodie Fache (Ambio, 2022)
Recognition of the multiple types of value of marine resources is crucial to help design locally meaningful and sustainable management approaches for marine and coastal habitats. There is a lack of information on the amount of living marine resources harvested by coastal communities in many Pacific Island Countries and Territories (PICTs), as well as on their economic and non-economic value. This paper explores the monetary, subsistence, and sociocultural value of selected marine resources (finfish and invertebrates) in Kadavu province, Fiji, based on a household survey and semi-structured interviews conducted in 2019 within one specific district. The paper provides estimates of the annual catch and monetary value of marine resources harvested by local communities at both the district and provincial levels, derived from catch and effort information collected from fishers and gleaners in situ. It also highlights the importance of integrating the sociocultural significance of marine resources into future value assessments.

Origin and expansion of the world’s most widespread pinniped: Range‐wide population genomics of the harbour seal ( Phoca vitulina ) - Xiaodong Liu; Suzanne Rønhøj Schjøtt; Sandra M. Granquist; Aqqalu Rosing‐Asvid; Rune Dietz; Jonas Teilmann; Anders Galatius; Kristina Cammen; Greg O’Corry‐Crowe; Karin Harding; Tero Härkönen; Ailsa Hall; et al. (Molecular Ecology, 2022)
The harbour seal ( Phoca vitulina ) is the most widely distributed pinniped, occupying a wide variety of habitats and climatic zones across the Northern Hemisphere. Intriguingly, the harbour seal is also one of the most philopatric seals, raising questions as to how it colonized its current range. To shed light on the origin, remarkable range expansion, population structure and genetic diversity of this species, we used genotyping‐by‐sequencing to analyse ~13,500 biallelic single nucleotide polymorphisms from 286 individuals sampled from 22 localities across the species’ range. Our results point to a Northeast Pacific origin of the harbour seal, colonization of the North Atlantic via the Canadian Arctic, and subsequent stepping‐stone range expansions across the North Atlantic from North America to Europe, accompanied by a successive loss of genetic diversity. Our analyses further revealed a deep divergence between modern North Pacific and North Atlantic harbour seals, with finer‐scale genetic structure at regional and local scales consistent with strong philopatry. The study provides new insights into the harbour seal's remarkable ability to colonize and adapt to a wide range of habitats. Furthermore, it has implications for current harbour seal subspecies delineations and highlights the need for international and national red lists and management plans to ensure the protection of genetically and demographically isolated populations.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Middle Pleistocene environments, landscapes and tephrostratigraphy of the Armenian Highlands: evidence from Bird Farm 1, Hrazdan Valley - Jenni E. Sherriff; Keith N. Wilkinson; Poppy Harding; Hayley Hawkins; Rhys G. O. Timms; Daniel S. Adler; Emily J. Beverly; Simon P. E. Blockley; Boris Gasparyan; Christina J. Manning; Darren Mark; Samvel Nahapetyan; et al. (Journal of Quaternary Science, 2022)
The significance of the southern Caucasus in understanding Pleistocene hominin expansions is well established. However, the palaeoenvironments in which Palaeolithic occupation of the region took place are presently poorly defined. The Hrazdan river valley, Armenian Highlands, contains a rich Palaeolithic record alongside Middle Pleistocene volcanic, fluvial and lacustrine strata, and thus offer exciting potential for palaeoenvironmental reconstruction. We present the first results of sedimentological, geochemical, tephrostratigraphical and biological (diatoms) study of the sequence of Bird Farm 1, located in the central part of the valley. These data show six phases of landscape development during the interval 440–200 ka. The sequence represents the first quantitative Pleistocene diatom record from the Armenian Highlands and the southern Caucasus, and indicates the persistence of a deep, stratified lacustrine system, with evidence for changing lake productivity that is tentatively linked to climate. Furthermore, major element chemical characterization of visible and crypto‐tephra horizons in the sequence enables the first stages of the development of a regional tephrostratigraphy. Together, the evidence from Bird Farm 1 demonstrates the importance of lacustrine archives in the region for palaeoenvironmental reconstruction and highlights the potential for linkages between archives on both a local and regional scale.

Invasive Nitrogen-Fixing Plant Amplifies Terrestrial–Aquatic Nutrient Flow and Alters Ecosystem Function - Simon D. Stewart; Megan B. Young; Jon S. Harding; Travis W. Horton (Ecosystems, 2019)

COLONIZATION HISTORY OF THE BALTIC HARBOR SEALS: INTEGRATING ARCHAEOLOGICAL, BEHAVIORAL, AND GENETIC DATA - Tero Harkonen; Karin C. Harding; Simon J. Goodman; Kerstin Johannesson (Marine Mammal Science, 2005)

The English national risk-reduction programme for preservation of sight in diabetes - Warren Gillibrand; Deborah Broadbent; Simon Harding; Jiten Vora (Molecular and Cellular Biochemistry, 2004)